PENGARUH KEBIJAKAN SUKU BUNGA BANK INDONESIA (BI Rate) TERHADAP NILAI TUKAR RUPIAH DAN RENTABILITAS BANK - Meliza SE.M.Com (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Global economic crisis in some European countries and United States has affected the value of  rupiah  exchange  rate.  Depreciation  of  rupiah  caused  some  industrial  sectors  that  used imported raw material face high production cost. Therefore, Bank Indonesia as central bank takes  some  actions  to  save  rupiah  value  by  increasing  the  interest  rate  in  order  to  raise capita inflow to Indonesia. This governance will also influence the banking sector especially the  fluctuation  of  bank’s  cost  of  fund  and  loan  interest  and  eventually  affect  bank’s rentability.  The  data  of  Indonesia  Interest  rate  and  Rupiah  exchange  rate  is  derived  from Bank  Indonesia  Website.  Meanwhile,  the  data  of  bank’s  rentability  (Return  on  Assets)  is derived from publicity of income statement and balance sheet of Bank Rakyat Indonesia and Bank  Danamon  period  July  2010-July  2013.  Furthermore,  this  research  use  multiple regression  method  as  research  methodology  that  measure  the  influence  of    interest  rate  to rupiah exchange rate and bank’s  rentability period July 2010-July 2013. The analysis data results  that  movement  of    interest  rate  of  Bank  Indonesia  (BI  Rate)  has  influence  to  rupiah exche rate about 48,4%. However, it does not have significant influence to bank’s rentability or only about 30%. Keywords : interest rate, rupiah exchange rate, bank’s rentability